Risk factors for lumbar disc herniation in adolescents and young adults: A case–control study - Qi, Le; Luo, Lijuan; Meng, Xianrong; Zhang, Jun; Yu, Tong; Nie, Xinyu; Liu, Qinyi (Frontiers in Surgery, 2023)
Background There is a limited understanding of the risk factors for lumbar disc herniation (LDH) in younger people, even though the evidence suggests that LDH is more prevalent in this population. This study aimed to comprehensively analyze the risk factors for LDH in adolescents and young adults. Methods The medical records of all patients were retrospectively reviewed with inclusion criteria of being younger than 25 years. Magnetic resonance imaging (MRI) was used to confirm LDH from September 2016 to September 2021. Furthermore, 104 healthy people in the same age range were enrolled as the control group from physical examination centers. Gender, BMI, smoking, drinking, genetic history, sitting posture, daily sitting time, traumatic history of the lower back, scoliosis, and daily exercise time were examined for all enrolled people. These factors were statistically analyzed to determine the high-risk factors. Results A total of 208 young individuals were enrolled in the present study. The mean age of the study group and the control group was 21.06 ± 3.27 years (range: 11–25 years) and 21.26 ± 2.23 years (range: 15–25 years), respectively. The result of the chi-squared test demonstrated that there was a significant difference in BMI of more than 30 (p < 0.001), genetic history (p = 0.004), sitting posture (p < 0.001), daily sitting time of more than 6 h (p < 0.001), and the history of low back trauma (p = 0.002). Additionally, multivariate logistic regression showed that these were high-risk factors for LDH, particularly the duration of daily sitting time (more than 6 h). Conclusions BMI of more than 30, genetic history, sitting posture, daily sitting time of more than 6 h, and a history of low back trauma are the high-risk factors for adolescents and young adults with LDH. Therefore, providing them with the proper guidance and education, particularly about the protection of the lower back and the reduction of spinal load, could play a key role in preventing and reducing LDH.